New sites of localisation of Pasteurella multocida B:2 in buffalo surviving experimental haemorrhagic septicaemia - Salleh, Annas; Saad, Mohd Zamri; Abdullah, Faez Firdaus Jesse; Zakaria, Zunita (BioMed Central, 2014)
Background: Haemorrhagic septicaemia (HS) is an acute septicaemic disease of buffalo and cattle caused by Pasteurella multocida B:2 and E:2. Field outbreaks of HS are known to result in localisation of bacteria in the tonsils of surviving buffalo, confirming that animals can become carriers and the role of respiratory tract in the transmission of the disease. This report describes additional sites of localisation of P. multocida B:2 in surviving buffalo following experimental induction of HS. Results: Following P. multocida B:2 infection, all calves in group 1 and one calf in group 2 that was allowed to commingle with infected calves from group 1 were euthanised within 48 h. Pasteurella multocida B:2 was detected from the nasal and rectal swab samples on days 5 and 6 from the remaining calves in group 2. The first injection of dexamethasone into the carrier animals resulted in reemergence in samples from the nose, rectum and vagina. However, subsequent dexamethasone injections failed to re-activate P. multocida B:2. When surviving carrier calves in group 2 were euthanised at the end of the experiment, P. multocida B:2 was detected in the lungs and various organs of the respiratory, gastrointestinal and urinary tracts. Conclusions: Commingling naive buffalo calves with calves acutely infected with P. multocida B:2 resulted in carriers among surviving buffalo. Pasteurella was found in various organs of the respiratory, gastrointestinal and urinary tracts, suggesting their role in the pathogenesis of HS.